Guidance Control for Fleet of Small Aerial Robots with Communication Restriction. Issue 22 (2018) - Sasaoka, Takashi; Suzuki, Satoshi
Abstract: In this paper, collision-free guidance control of multiple small aerial robots is designed. Collision avoidance should be considered in the operation of a fleet of aerial robots. A guidance control system using a distributed model predictive control (DMPC) is proposed to realize the collision avoidance. A constraint of the relative position vector between each robot is considered in the design for efficient avoidance. Small multi-rotor helicopter is considered as controlled object, and the guidance control system is designed by using the translational model of the helicopter. The robots exchange information about current state and optimal input sequence each other for calculating the predictive trajectory of others. Based on the calculated trajectories, each helicopter solves its local optimization problem. Here, sharing the velocity information is difficult because calculation processing capability of the small sensor and communication capability among the robots are strictly restricted. Therefore, a dynamic compensator for velocity compensation is introduced. By introducing the dynamic compensator, collision avoidance using only exchange on the position and the input sequence information is accomplished without exchanging velocity information. The effectiveness of the proposed control system is verified by numerical simulations and flight experiment.